Secure and efficient two-party collaborative SM9 signature scheme suitable for smart home - Shuang Gen Liu; Ru Liu; Si Yuan Rao (Journal of King Saud University: Computer and Information Sciences)
The smart home usually has poor security and is vulnerable to attack since it adopts embedded processors that are limited by volume and power consumption. To improve the communication security of the smart home system, identity-based signature schemes are widely used in wireless network communications. However, the user’s signature private key is generally stored in a single device, it is easy to be stolen by attackers to control the smart home devices. To reduce the risk of leakage of the signature private key, a two-party collaborative signature scheme based on the SM9 algorithm is proposed in this paper. The user’s signature private key is generated through the collaboration of the two-party key generation center (KGC), and the integer secrets related to the signature private key are stored in two devices respectively. During the signing process, the two devices sign collaboratively to prevent the complete private key from being leaked. The security of the scheme is proved in the random oracle model. Theoretical analysis and experimental results show that our proposed scheme can achieve higher security with lower computation cost and communication cost when compared with the existing two-party SM9 signature schemes.